2015
DOI: 10.1155/2015/518179
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Physician Productivity and Self-Sustaining Revenue Generation in a Free-Standing Emergency Department Medical Scribe Model

Abstract: Objectives. A free-standing emergency department (FSED) is a facility that provides comprehensive emergency medical care similar to a traditional emergency department but is not attached to a hospital campus. Medical scribes are increasingly likely to work in free-standing emergency departments. The purpose of this study was to retrospectively investigate the benefits of a scribe program in an FSED.Methods. A retrospective, Institutional Review Board-approved analysis from December 1, 2013, to February 1, 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…9-11 Benefits have been demonstrated in improvements to patient throughput; documentation; patient outcomes; hospital billing and revenue; resident training; and provider, consultant, and patient satisfaction. 6,12,13 Although not every study demonstrated that scribes provided a significant benefit in terms of the study's primary outcome (eg, length of stay), no study reported inferior outcomes associated with the use of scribes.…”
Section: Introductionmentioning
confidence: 99%
“…9-11 Benefits have been demonstrated in improvements to patient throughput; documentation; patient outcomes; hospital billing and revenue; resident training; and provider, consultant, and patient satisfaction. 6,12,13 Although not every study demonstrated that scribes provided a significant benefit in terms of the study's primary outcome (eg, length of stay), no study reported inferior outcomes associated with the use of scribes.…”
Section: Introductionmentioning
confidence: 99%
“…While we were not able to identify a "gold-standard" approach for scribe training (eg, a generally agreed-upon competency model), there are some commonalities across different training programs offered by commercial scribing companies 20,24,25,[41][42][43][44][45][46][47][48][49][50][51][52] or by HCOs. 19,22,38,44,45,[53][54][55][56][57][58][59][60][61] Most of the training programs described in the literature are divided into 2 phases: an initial didactic phase and an applied, "hands-on" phase. In the didactic phase, written or online tutorials, 45,53,62,63 quizzes, 56 and clinical simulations 20,25,40,42,44,46,47,54,57,58,62 are used to teach the trainee on clinical procedures, Healthcare Insurance Portability and Accountability Act compliance, medical terminologies, documentation structure, billing and coding processes, and use of clinical inf...…”
Section: Training Certification and Managementmentioning
confidence: 99%
“…Medical scribes in the United States are commonly managed by commercial scribing companies as subcontractors, 20,24,25,38,41-47, 49-52,65,70 even though some are directly employed by HCOs. 19,22,38,44,45,[53][54][55][56][57][58][59][60][61]71 Within an HCO, a scribe is assigned either to an individual provider (the "one-to-one" model) 50 or to a group of providers (the "one-to-many" model), 25 or is available as part of a pooled resource assigned dynamically based on matched schedules (the "many-to-many" model). 49 Use of these management models varies to a great extent depending on the preference of the HCO or of the scribing company.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation